DESIGN OF MEDAN CITY MARKET PD PERFORMANCE MEASUREMENT USING BALANCED SCORECARD METHOD - Rika Puspita Dewi; Nazaruddin; Yeni Absah (Journal of Accounting Research, Utility Finance and Digital Assets, 2023)
This research aims to design a performance measurement for PD market in Medan City using the balanced scorecard method. The sampling technique used was convenience sampling, namely a sampling method whose respondents were people who volunteered for certain reasons. As the name suggests, this method selects samples from a population (people or events) whose data are easily obtained by researchers. The type of data in this research uses primary data and secondary data. Primary data is data collected by researchers directly from respondents. The research results show that from a financial perspective the results obtained for Net Profit Margin (NPM) are in the poor category because they are below >5%, Likewise, GPM is in a poor category because it is below 8.3%. From the perspective of PD Pasar Kota Medan customers, seen from the analysis, it shows satisfied results. By carrying out overall calculations using the Multiattribute Attitude Model (MAM) method, it shows a result of 92.52 and based on the categorization, it is included in the very satisfied range. From the perspective of PD Pasar Kota Medan's internal business processes, seen from the analysis, it shows good results. PD Pasar Kota Medan is able to carry out innovation processes, operational processes and after-sales processes well, and from the perspective of learning and growth, PD Pasar Kota Medan, seen from its analysis, shows very satisfactory results.